PERSEPSI MASYARAKAT HUTAN MANGROVE BAHOWO DI KELURAHAN TONGKAINA KECAMATAN BUNAKEN KOTA MANADO - Enggelina ., Baraoh; Jenny ., Baroleh; Welson Marthen Wangke (Sam Ratulangi University, 2019)
The purpose of the study was to determine the public perception of the Bahowo mangrove forest. This research was conducted in Bahowo, Tongkaina Sub-District, Bunaken District, Manado City. The study lastedfor 3 (three) months from August to November 2018 starting from preparation to writing the final report. The selection of respondents was done purposevely.This study used primary data and secondary data. Primary data was obtained through direct interviews with 20 respondents based on a list of prepared statements. Secondary data was obtained through documentation from agencies related to this study, among others, at the Tongkaina District Office in Bunaken District, Manado City, local bookstore and the internet using a google search engine to access scientific journal articles and thesis from others universities regarding people's perceptions of mangrove forests. This research showed that the community has positve perceptions of mangrove forests. Bahowo in Tongkaina Sub-District, Bunaken Sub-District, Manado City as a whole stated that he agreed with a total score of 1,714 judgments from the statements conveyed by the community through direct interviews and by calculating the overall score to determine the community's perception of mangrove forests. The community argued that mangrove forests play a very important role for local communities such as protecting from the dangers of high waves and tsunami hazards.*eprm*